PENDEKATAN ANTROPOLOGIS DALAM METODE STUDI ISLAM - Bayu Bambang Nurfauji; Yunia Aspiani; Nurmalasari; Yuliana Fahira; Ida Dalilah; Lia Andayani (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This theory discusses the relevance and application of the anthropological approach in Islamic studies. This approach offers a unique way to understand Islam not only as a set of theological doctrines or sacred texts but also as a living and dynamic cultural practice experienced by Muslims in their daily lives. Through the use of ethnographic methods and participant observation, anthropology enables researchers to understand how Muslims in different parts of the world interpret, practice, and make meaning of their religion in diverse social, cultural, and political contexts. This article also discusses how the anthropological approach can help overcome excessive generalizations and stereotypes about Islam and promote a deeper understanding of the variations and diversity in Muslim religious practices. Additionally, this article examines the integration of the anthropological approach with other disciplines, such as sociology, history, and legal studies, to provide a more comprehensive understanding of Islam. Finally, this article highlights the contemporary relevance of the anthropological approach in addressing the challenges faced by Muslims, such as extremism, radicalism, and Islamophobia. (Bowen, 2012; Marranci, 2008)